2014
DOI: 10.1371/journal.pone.0098353
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplast Genome of Hyoscyamus niger and a Phylogenetic Study of the Tribe Hyoscyameae (Solanaceae)

Abstract: The tribe Hyoscyameae (Solanaceae) is restricted to Eurasia and includes the genera Archihyoscyamus, Anisodus, Atropa, Atropanthe, Hyoscyamus, Physochlaina, Przewalskia and Scopolia. Even though the monophyly of Hyoscyameae is strongly supported, the relationships of the taxa within the tribe remain unclear. Chloroplast markers have been widely used to elucidate plant relationships at low taxonomic levels. Identification of variable chloroplast intergenic regions has been developed based on comparative genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 49 publications
(98 reference statements)
5
47
0
Order By: Relevance
“…This editing is controlled by the nuclear genome, opening the door to nuclear-cytoplasmic incompatibilities (Schmitz-Linneweber et al, 2005). The Nt-derived nuclear-encoded editing machinery in the cybrid Nt(+Hn) faces the challenge of editing three Hn-specific sites of chloroplast RNA editing, one in each of three genes ( ndhA , ndhD , and rpoB ) in which the cybrid (this study) and Hn (Sanchez-Puerta & Abbona, 2014) cpDNAs are predicted to undergo RNA editing at sites at which Nt cpDNA encodes a T and does not require editing. Those edits restore what would otherwise be non-synonymous changes at highly conserved amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This editing is controlled by the nuclear genome, opening the door to nuclear-cytoplasmic incompatibilities (Schmitz-Linneweber et al, 2005). The Nt-derived nuclear-encoded editing machinery in the cybrid Nt(+Hn) faces the challenge of editing three Hn-specific sites of chloroplast RNA editing, one in each of three genes ( ndhA , ndhD , and rpoB ) in which the cybrid (this study) and Hn (Sanchez-Puerta & Abbona, 2014) cpDNAs are predicted to undergo RNA editing at sites at which Nt cpDNA encodes a T and does not require editing. Those edits restore what would otherwise be non-synonymous changes at highly conserved amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Graphical genome maps were generated using OGDraw software (Lohse et al, 2007). The cybrid cpDNA was not annotated because it is identical to that of H. niger (Sanchez-Puerta & Abbona, 2014). Non-synonymous sites of RNA editing were predicted using PREP-Mt (Mower, 2005) with a cutoff value of 0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA editing sites obtained from B. flabellifer (this study), Cocos nucifera (identified by Next Generations Sequencing or NGS; Huang et al, 2013) and Elaeis guineensis (by NGS; Uthaipaisanwong et al, 2012), in total 53 sites, were compared to those of other 15 plant species. These included six monocots: S. polyrhiza (21 sites by NGS), P. aphrodite (13 sites by direct cDNA sequencing), Z. mays (13 sites by direct cDNA sequencing), O. sativa (14 sites by direct cDNA sequencing), S. officinarum (12 sites by NGS) and H. vulgare (8 sites by direct cDNA sequencing), six dicots: A. thaliana (10 sites by direct cDNA sequencing), P. sativum (7 sites by direct cDNA sequencing), A. belladonna (8 sites by direct cDNA sequencing), H. niger (8 sites by NGS), J. curcas (7 sites by NGS), N. tabacum (10 sites by direct cDNA sequencing) and two gymnosperms: C. taitungensis (5 sites by using CURE-Chloroplast software and direct sequencing) and Pinus thunbergii (0 sites by direct cDNA sequencing) (Wakasugi et al, 1996;Corneille et al, 2000;Sasaki et al, 2003;Inada et al, 2004;Zeng et al, 2007;Asif et al, 2010;Uthaipaisanwong et al, 2012;Huang et al, 2013;Sanchez-Puerta and Abbona, 2014;Wang et al, 2015;He et al, 2016). The list of genes is presented in Table S2.…”
Section: Comparison Of Rna Editing Sites Among Plant Speciesmentioning
confidence: 99%
“…The genes psbT, rpl2, and ndhD had the alternative start codon ACG, and rps19 started with GTG. Use of ACG and GTG as start codons is common for a variety of genes in the chloroplast genomes of land plants [17][18][19][20]. Finally, the cemA gene was identified as a pseudogene with a premature stop codon in the F. cirrhosa cp genome.…”
Section: Chloroplast Genome Organization Of Two Fritillaria Speciesmentioning
confidence: 99%